Aromatic molecules as sustainable lubricants explored by ab initio simulations. (25th January 2023) - Peeters, Stefan; Losi, Gabriele; Loehlé, Sophie; Righi, M.C.
Abstract: In pursuit of sustainable lubricant materials, the in situ formation of graphitic material has been shown to effectively reduce friction at metallic interfaces. Aromatic molecules are perfect candidates for the formation of carbon-based tribofilms due to their inertness and chemical structure. We selected a group of common aromatic compounds, which are still unexplored in tribology, and we investigated their capability to reduce the adhesion of sliding iron interfaces. Ab initio molecular dynamics simulations show that hypericin, a component of St. John's wort, can effectively separate the mating iron surfaces better than graphene. The size of this molecule, combined with the reactivity and the hindrance of its moieties, plays an important role in maintaining large interfacial distances. Stacked hypericin molecules can easily slide on top of each other due to the intermolecular repulsion arising in the presence of load. The decomposition of the lateral groups of hypericin observed in the dynamic simulations suggests that the polymerization of several molecules can occur in tribological conditions. All these results pave the way for promising alternatives to commonly employed friction modifiers. Graphical abstract: Highlights: Common aromatic molecules can be used as sustainable lubricants. Hypericin and benzyl benzoate are the most promising compounds. Their size and steric hindrance favor the interfacial separation. A monolayer of these compounds reduces interfacial adhesion better than graphene.